Tissue distribution of lycopene in ferrets and rats after lycopene supplementation - Ferreira, Ana Lúcia dos Anjos [UNESP]; Yeum, Kyung-Jin; Liu, Chun; Smith, Donald; Krinsky, Norman I.; Wang, Xiang-Dong; Russell, Robert M. (My University, 2000)
To determine lycopene uptake and tissue distribution in ferrets (Mustela putorius furo) and F344 rats, we supplemented orally 4.6 mg/(kg body wt-d) lycopene in a tomato oleoresin-com oil mixture (experimental groups). After 9 wk of supplementation, the animals were killed and blood and organs were collected. Plasma and tissue carotenoids were extracted and measured using HPLC. Mean concentrations of lycopene (nmol/kg wet tissue) in saponified tissues of ferrets were as follows: liver 933, intestine 73, prostate 12.7 and stomach 9.3. Levels of lycopene (nmol/kg wet tissue) in saponified tissue of rats were as follows: liver 14213, intestine 3125, stomach 78.6, prostate 24 and testis 3.9. When these organs were extracted without saponification, the lycopene levels were lower, except for rat testis. All-translycopene was the predominant isomer found in tomato oleoresin and in the majority of rat tissues, whereas cislycopenes were predominant in rat prostate and plasma. This pattern was reversed in ferrets. The results show the following: 1) lycopene from tomato oleoresin is absorbed and stored primarily in the liver of both animals; 2) saponification generally improves the extraction of lycopene from most tissues of both animals; 3) cis-lycopene and all- translycopene are the predominant isomers in ferret and rat tissues, respectively; and 4) rats absorb lycopene more effectively than ferrets.
Keywords: Ferrets; Lycopene; Prostate; Rats; Testis; carotenoid; corn oil; lycopene; resin; animal experiment; animal tissue; cis isomer; controlled study; diet supplementation; extraction; ferret; high performance liquid chromatography; intestine; liver level; male; nonhuman; prostate; rat; stomach; testis; tissue distribution; tissue level; tomato; trans isomer; Administration, Oral; Animals; Antioxidants; Carotenoids; Chromatography, High Pressure Liquid; Dietary Supplements; Intestinal Absorption; Male; Rats, Inbred F344; Species Specificity; Tissue Distribution; Animalia; Lycopersicon esculentum; Mustela; Mustela putorius furo; Zea mays